INCLUSIVE PRACTICES OF ISLAM IN INDIA: CHALLENGING EXCLUSIVE NOTIONS - K. M. ZIYAUDDIN, (IJRDO - Journal of Business Management, 2018)
Muslims in India have been a heterogeneous community for several centuries. The arrival of Muslim in India has been misunderstood as aggression and invasion on the Indian soil which is not true in any sense. Islam never reached in Indian sub-continent by invasion and force rather it was though trade and commerce by the Arab. The Arab began their journey to travel in different parts of the world. The arrival of Islam in Kerala is seen as the first interaction of Muslims with Indian religious groups mainly Hindus. The significant contribution of inclusive practices in the trade relations can be attributed to be the revolutionary steps. The trade in India had been caste based where not everyone was allowed to engage into whereas a Muslim would buy and sale their goods to any buyers who had capacity to pay without any discrimination and distance. This also broke the notion of pollution and purity amongst the Indian